2006
DOI: 10.1108/09564230610667122
|View full text |Cite
|
Sign up to set email alerts
|

Call centre management: responsibilities and performance

Abstract: Purpose: to investigate call centre management from the perspective of the managers, particularly what the key management responsibilities are in managing call centres and the key performance indicators used in managing call centres. Methodology: a survey of call centre managers, followed by in-depth interviews. Findings: there is confusion over the strategic intent of call centres. Centres are primarily used by organisations as a means of reducing costs, with customer service delivery a secondary consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 9 publications
2
73
0
Order By: Relevance
“…Broderick et al (2010) reported that the imposition of prescribed elements of KPI systems on organizational activities did not generate commitment or encourage continuous improvement and argued that less cumbersome measurement models are required to allow firms to apply benchmarking and quality ideas flexibly. Robinson and Morley (2006) also argued that the achievement of the relevant KPI became a goal in its own right and that monitoring these KPIs becomes the "main game" in the climate of quantitative performance measures. As such, it should be noted that performance measurement using KPIs comes with potential risk factors.…”
Section: Key Performance Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Broderick et al (2010) reported that the imposition of prescribed elements of KPI systems on organizational activities did not generate commitment or encourage continuous improvement and argued that less cumbersome measurement models are required to allow firms to apply benchmarking and quality ideas flexibly. Robinson and Morley (2006) also argued that the achievement of the relevant KPI became a goal in its own right and that monitoring these KPIs becomes the "main game" in the climate of quantitative performance measures. As such, it should be noted that performance measurement using KPIs comes with potential risk factors.…”
Section: Key Performance Indicatorsmentioning
confidence: 99%
“…If KPIs are simply established and everything else is left to the arbitrary judgment of the managers, it is highly likely that the KPIs become short-term goals and that managers and salespersons only commit themselves to achieving those goals (Robinson and Morley 2006).…”
Section: Supportive Supervision and Knowledge Sharingmentioning
confidence: 99%
“…It is possible that capability control strategies were ineffective due to the overwhelming levels of outcome control. Several authors (e.g., Robinson and Morley, 2006;Feinberg et al, 2000) have, in fact, commented about the extreme levels of performance monitoring in call centres.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…A common way to define Service Level is by looking at the fraction of requests answered within a defined time frame (usually called the Acceptable Waiting Time-AWT). A typical value is that 80% of all calls has to be answered in 20 seconds [30], but for the SPUN case is not important to be fast, but to respond completely and correctly. According to the manager, a particularly interesting indicator is the service level for complex requests.…”
Section: What-if Analysismentioning
confidence: 99%